Popular music the key concepts - Shuker, Roy (Routledge key guides, 2017)
Now in an updated 4th edition, this popular A-Z student handbook provides a comprehensive survey of key ideas and concepts in popular music culture. With new and expanded entries on genres and sub-genres the text comprehensively examines the social and cultural aspects of popular music.